Inference Concerning the Number of Factors in a Multivariate Nonparametric Relationship - Donald, Stephen G. (Econometrica, 1997)
This paper considers the problem of determining the number of factors in a multivariate nonparametric relationship. The definition of factors given is broad enough to encompass a number of potential applications in econometrics, including inferring the rank of demand, consistent tests for lack of identification in linear instrumental variable models, and testing arbitrage pricing theory. The paper gives both series and kernel methods for testing hypotheses concerning, and consistent estimation of, the number of factors. The methods are compared in a small simulation study and in an application to determining the rank of demand systems.